Highly efficient 5' capping of mitochondrial RNA with NAD+ and NADH by yeast and human mitochondrial RNA polymerase - Bird, Jeremy G.; Basu, Urmimala; Kuster, David; Ramachandran, Aparna; Grudzien-Nogalska, Ewa; Towheed, Atif; Wallace, Douglas C; Kiledjian, Megerditch; Temiakov, Dmitry; Patel, Smita S; Ebright, Richard H; Nickels, Bryce E (eLife, 2018)
Bacterial and eukaryotic nuclear RNA polymerases (RNAPs) cap RNA with the oxidized and reduced forms of the metabolic effector nicotinamide adenine dinucleotide, NAD+ and NADH, using NAD+ and NADH as non-canonical initiating nucleotides for transcription initiation. Here, we show that mitochondrial RNAPs (mtRNAPs) cap RNA with NAD+ and NADH, and do so more efficiently than nuclear RNAPs. Direct quantitation of NAD+- and NADH-capped RNA demonstrates remarkably high levels of capping in vivo: up to ~60% NAD+ and NADH capping of yeast mitochondrial transcripts, and up to ~15% NAD+ capping of human mitochondrial transcripts. The capping efficiency is determined by promoter sequence at, and upstream of, the transcription start site and, in yeast and human cells, by intracellular NAD+ and NADH levels. Our findings indicate mtRNAPs serve as both sensors and actuators in coupling cellular metabolism to mitochondrial transcriptional outputs, sensing NAD+ and NADH levels and adjusting transcriptional outputs accordingly.